The Urgency of Religious Marriage Registration in Population Administration Regulations for Legalization and Granting Permits - Palilati, Nur Fika; Kasim, Nur Mohamad; Abdussamad, Zamroni (Universitas Negeri Gorontalo, 2025)
The purpose of this study is to further analyze the urgency of recording interfaith marriages in population administration regulations for legalization and licensing. The research method used is a normative legal research method with a statutory approach. The results of this study found that the registration of interfaith marriages is an important aspect to ensure the formal legality and protection of the civil rights of couples, such as inheritance rights, joint property, and child status. However, interfaith couples often face legal obstacles because population administration regulations do not explicitly accommodate interfaith marriages. As a result, they often have to resort to the courts to obtain legalization. The role of the court is crucial in granting permission for registration, although decisions vary depending on the interpretation of the judge. While some are successful, the process still poses legal and social challenges for couples.